Hubungan Intensitas Keikutsertaan Hypnobirthing dengan Tingkat Kecemasan Ibu Hamil di Gianyar - Martalisa, Winda; Budisetyani, I Gusti Ayu Putu Wulan (Jurnal Psikologi Udayana, 2013)
During the pregnancy, a mother has experienced a significant changes to the physiological function and their psychological that causing an anxiety. Pregnant women who experience excessive anxiety during pregnancy until the delivery would cause pain during childbirth and this must be addressed, namely pregnant women should have the peace that the birth process to be smooth. Many natural ways that can be used to help reduce maternal anxiety, one way is to follow the hypnobirthing techniques. There are a lot of natural ways that can be used to help them decreased their anxiety. One thing that can be done is following the hypnobirthing technique. The aim of this research is to observed the relationship of hypnobirthing participation intensity with the anxiety levels of pregnant woman. The subject of this research were 20 pregnant women who take the hypnobirthing techniques with a gestational age around 7-9 months in Gianyar. The sample were selected using total sampling method. The anxious scale of the subjects were pointing to the aspects that stated by Daradjat. The intensity of participation in hypnobirthing  is accounted by  present list. The method of analyzing data in this research was by using the spearman non-parametric analysis. This research uses unused and try out the validity of the results obtained from 0,270 to 0.738, while the value of reliability for (a = 0.908). The result of the test analysis data is, there was a significant nominal for p=0,001 (p<0,05) with coefficient correlation value it is  -689.  That coefficient correlation has indicated that there was a negative relation between the anxious variable, to the participation of hypnobirthing intensity. Therefore, the hypothesis (Ha) in this research was acceptable. That is, if the intensity of the routine participation hypnobirthing  the anxiety level will decrease. Support of the role of fathers and families in the process of hypnobirthing is highly recommended for pregnant women in order to obtain better results.   Keywords: pregnancy women, anxiety, hypnobirthing